Compensation-Based Intervention to Improve Activities of Daily Living in Individuals with Stroke: Randomized Controlled Pilot Study. - Kaya Ozturk, Leyla; Huri, Meral; Umay, Ebru (NeuroRehabilitation, 2026)
Objective: Individuals with stroke frequently experience limitations in activities of daily living, and compensation-based approaches have the potential to enhance functional adaptation. This study aimed to develop and evaluate the feasibility and preliminary effects of a novel intervention, Compensation-Based Problem-Solving Therapy (CBPST), on participation and activities of daily living in individuals with stroke. Methods: CBPST was developed by trained occupational therapists, emphasizing in Occupational Adaptation Model and compensatory strategies. The CBPST was delivered individually in five sessions weekly (during four week and approximately 40 min)and including identifying the problem, developing strategies, selecting strategy and implementing and evaluating the selected strategy. Participants were randomly assigned to intervention or control group. This study involved 50 individuals with stroke assigned to either an intervention (n = 24 and mean age 54.58 ± 7.86) or control group (n = 26 and mean age 54.56 ± 7.09). Outcomes were assessed at baseline and immediately post-intervention using the Functional Independence Measure (FIM), Lawton-Brody Instrumental Activities of Daily Living (Lawton-Brody IADL), Frenchay Activity Indeks (FAI) and the Canadian Occupational Performance Measure (COPM). Statistical analyses included Wilcoxon signed-rank, Mann-Whitney U tests and effect sizes. Results: Both groups showed significant improvements (p < 0.05) in participation and activities of daily living. Effect size estimates in the intervention group indicated moderate to large clinical effects across outcome measures (COPM performance and satisfaction: 0.62; FIM: 0.62; Lawton–Brody IADL: 0.53; FAI: 0.55), supporting the preliminary efficacy of CBPST. Conclusion: CBPST appears to be a feasible and promising approach to enhance adaptive participation after stroke by integrating problem-solving and compensatory strategies. Larger studies are warranted to confirm its clinical effectiveness.